DEREGULATION AND THE 2008 FINANCIAL CRISIS IN AMERICA - Chen, Jeffrey (PEOPLE: International Journal of Social Sciences, 2020)
This paper strives to understand the role of the deregulation movement in the 2008 financial crisis, which almost destroyed the US economy. Financial regulations created a legal barrier that safeguarded the US economy for four decades after the Great Depression. With the intent of improving the competitiveness of the US financial industry in the global economy, the US government adopted many deregulatory measures from the 1980s to the 2000s. For a short while, financial deregulation stimulated impressive economic growth. However, this temporary prosperity was subsequently overshadowed by the greatest financial disaster in modern history. This paper shows how the financial regulatory edifice was initially established after the Great Depression and how it was gradually eroded by the deregulation movement, which ultimately contributed to the 2008 financial crisis. Also, the remedies and new regulations that were introduced during and after the crisis are discussed.